Economic and Social Dimensions of Sugar Crop Cultivation in Egypt: A Comparative Analysis of Sugarcane and Sugar Beet Production - F. O. Alsubaie, Naser; Abdel Kareem, Nessrien; A. M. Moursy, Mohamed; A. Ameen, Faleh; M.M. HAMED, Lamy (Cuestiones de Fisioterapia, 2024)
This study examines the economic and social implications of reducing the agricultural area devoted to sugarcane cultivation, expanding sugar beet cultivation, and exploring alternative cropping structures to meet Egypt’s sugar production targets over the past decade. The research focuses on governorates with concentrated sugarcane cultivation in Upper and Middle Egypt, specifically Aswan and Qena (representing Upper Egypt) and Minya (representing Middle Egypt).